Net Neutrality Under EU Law – a Hindrance to 5G Success - Raimo Kantola (International Telecommunications Society (ITS), 2019)
EU has adopted a law on Net Neutrality (NN) ruling that Internet access providers should treat all traffic equally irrespective of sender, receiver, content, service, application or device in use. The 5G community is developing a network that can be tailored to a use case, meaning that it intends to treat traffic differently for each use case. Tailoring can be at least in terms of traffic management, allocated types and amount of resources, redundancy, particular forms of security etc. Moreover, 5G network uses network function virtualization, i.e. cloud technology is applied to run the network itself while the law on NN does not mention the concept of the cloud. The interpretation is that if a cloud platform is owned by the Internet access provider, the cloud is just a part of the network and under the NN regulation. At the same time if a cloud-based computer is owned by a cloud or content provider, it is a terminal and thus not regulated. 5G introduces the idea of edge computing (EC) that can use virtualization and allows special treatment for some applications or services. This paper explores how significant is this controversy between the new concepts of networking in 5G and the EU regulation and what is its possible impact on the network providers. The paper studies to what extent and how the 5G ideas can be applied under the EU law and whether something should be done about the law and in particular the Guidelines that have been published by the Body of European Regulators for Electronic Communications (BEREC) to clarify the implementation of the law. Finally, we discuss the possible impact of the law on industry structure.
Keywords: 330; Net neutrality; 5G; slicing; traffic treatment; traffic management; security; specialized service